Didactisation d’éléments du patrimoine linguistique de la Caraïbe dans l’apprentissage du français langue étrangère en Guadeloupe : retour d’expérience - Frédéric Beaubrun (Études Caribéennes)
Our paper was conceived inside the linguistic integration for migrant people system which is official in Guadeloupe French West Indies department. We are asking about artistic and creative learning in linguistic didactics and we look about the place of the cultural heritage inside the people’s learning system. The line of reflection which guides our research is an approach which takes into account the already existing linguistic and cultural characteristics of the learners with the aim to identify and use a certain number of making more sense processes to make French language learning easier. Our dynamics is based on former research in sociolinguistics and didactics. Productions are analyzed in learner’s discourses who try to integrate themselves in the French republican system by an official program. Nevertheless, our approach can be considered as original in spite of this prescriptive situation as we use some musical and popular tales given to be described as pedagogic and linguistic tools.